Clinicopathologic analysis of TAFRO syndrome demonstrates a distinct subtype of HHV‐8‐negative multicentric Castleman disease. Issue 2 (February 2016) - Iwaki, Noriko; Fajgenbaum, David C.; Nabel, Christopher S.; Gion, Yuka; Kondo, Eisei; Kawano, Mitsuhiro; Masunari, Taro; Yoshida, Isao; Moro, Hiroshi; Nikkuni, Koji; Takai, Kazue; Matsue, Kosei; et al.
Abstract : Multicentric Castleman disease (MCD) describes a heterogeneous group of disorders involving systemic inflammation, characteristic lymph node histopathology, and multi‐organ dysfunction because of pathologic hypercytokinemia. Whereas Human Herpes Virus‐8 (HHV‐8) drives the hypercytokinemia in a cohort of immunocompromised patients, the etiology of HHV‐8‐negative MCD is idiopathic (iMCD). Recently, a limited series of iMCD cases in Japan sharing a constellation of clinical features, including thrombocytopenia (T), anasarca (A), fever (F), reticulin fibrosis (R), and organomegaly (O) has been described as TAFRO syndrome. Herein, we report clinicopathological findings on 25 patients (14 males and 11 females; 23 Japanese‐born and two US‐born), the largest TAFRO syndrome case series, including the first report of cases from the USA. The median age of onset was 50 years old (range: 23–72). The frequency of each feature was as follows: thrombocytopenia (21/25), anasarca (24/25), fever (21/25), organomegaly (25/25), and reticulin fibrosis (13/16). These patients frequently demonstrated abdominal pain, elevated serum alkaline phosphatase levels, and acute kidney failure. Surprisingly, none of the cases demonstrated marked hypergammoglobulinemia, which is frequently reported in iMCD. Lymph node biopsies revealed atrophic germinal centers with enlarged nuclei of endothelial cells and proliferation of endothelial venules in interfollicular zone. 23 of 25 cases were treated initially with corticosteroids; 12 patients responded poorly and required further therapy. Three patients died during the observation period (median: 9 months) because of disease progression or infections. TAFRO syndrome is a unique subtype of iMCD that demonstrates characteristic clinicopathological findings. Further study to clarify prognosis, pathophysiology, and appropriate treatment is needed. Am. J. Hematol. 91:220–226, 2016. © 2015 Wiley Periodicals, Inc.